2021
DOI: 10.3390/nu13124339
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Serum Angiopoietin-like Proteins 3 and 8 and Atherogenic Lipid Biomarkers in Non-Diabetic Adults Depends on Gender and Obesity

Abstract: Hypertriglyceridemia is an independent risk factor for coronary artery disease. Lipoprotein lipase (LPL) plays an essential role in the metabolism of triglyceride-rich lipoproteins (TRLs). Angiopoietin-like proteins ANGPTL3 and ANGPTL8 are shown to be important regulators of LPL activity. Increased concentrations of these proteins may reflect cardiovascular risk, and the treatment of patients with dyslipidemia with ANGPTLs inhibitors may decrease this risk. We assessed the gender-specific relationships of seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The data so far are controversial; some but not all reports demonstrated higher levels of ANGPTL8 in obese patients than in non-obese. In the previous study from our group, we noticed significantly higher levels of ANGPTL8 in apparently healthy women with obesity whereas ANGPTL3 levels were comparable [21].…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…The data so far are controversial; some but not all reports demonstrated higher levels of ANGPTL8 in obese patients than in non-obese. In the previous study from our group, we noticed significantly higher levels of ANGPTL8 in apparently healthy women with obesity whereas ANGPTL3 levels were comparable [21].…”
Section: Discussionsupporting
confidence: 43%
“…This analysis was adjusted for several variables but not age and gender [20]. In our previous study we observed a significant positive correlation between ANGPTL3 and CRP and BMI in males whereas in females no relationship between these variables was found [21]. Certainly, the mechanisms linking ANGPTL3 and low-grade inflammation remain unclear and require further studies; however, we suggest that gender-dependent differences may contribute.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…To date, there have been no studies on the putative associations between DOCK6 and diabetes or CKD. However, multiple studies have revealed that the levels of ANGPTL8 are higher in patients with diabetic nephropathy and obesity as well as positively correlated with atherogenic markers and carotid intima-media thickness [55][56][57][58]. Another study by Zou et al revealed that older subjects with higher circulating ANGPTL8 levels were at an increased risk of kidney function decline, which might suggest a role of ANGPTL8 in the pathogenesis of CKD [59].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in apparently healthy subjects [61] and patients with diabetes [62] have reported a positive association between increased plasma ANGPTL3 and sdLDL particles. These findings suggest possible beneficial effects of ANGPTL3 inhibition on sdLDL, which should be verified in the future.…”
Section: Evinacumabmentioning
confidence: 99%